Violence against peasants in Maranhão during the 1980s and 1990s (Research, Society and Development, 2022)
This work aims to problematize and interpret data about land conflicts that occurred in the state of Maranhão during the last two decades of the twentieth century. A period in which violence against peasants was latent, both by the criminal attacks of landowners, and by the denial of action to mediate conflicts by the state. The methodological approach took into account the researchers' experiences in this area of ​​knowledge, the survey and analysis of the reports produced by the Pastoral Land Commission (CPT) throughout the investigated period and the bibliographic productions on the topic under discussion. The results highlighted in the text show, in numbers, the deaths, the violence and the omission of the state towards the peasants of Maranhão who are victims of the greed of the farmers and agribusiness. Resistance to the various forms of violence suffered by peasants is highlighted in our narrative in the strength that emerges from organizations and Social Movements in partnership with the church, the CPT and the desire to fight and remain on the land. A desire that has been decisive in advancing peasant conquests over more than three decades of struggle in the countryside.